Regional sex differences in neurochemical profiles of healthy mice measured by magnetic resonance spectroscopy at 9.4 tesla - Tkáč, Ivan; Xie, Tiankai; Shah, Nitya; Larson, Sarah; Dubinsky, Janet M.; Gomez-Pastor, Rocio; McLoughlin, Hayley S.; Orr, Harry T.; Eberly, Lynn E.; Öz, Gülin (Frontiers in Neuroscience, 2023)
Objective: To determine sex differences in the neurochemical concentrations measured by in vivo proton magnetic resonance spectroscopy ( 1 H MRS) of healthy mice on a genetic background commonly used for neurodegenerative disease models.Methods: 1 H MRS data collected from wild type mice with C57BL/6 or related genetic backgrounds in seven prior studies were used in this retrospective analysis. To be included, data had to be collected at 9.4 tesla magnetic field using advanced 1 H MRS protocols, with isoflurane anesthesia and similar animal handling protocols, and a similar number of datasets from male and female mice had to be available for the brain regions analyzed. Overall, 155 spectra from female mice and 166 spectra from male mice (321 in total), collected from six brain regions (brainstem, cerebellum, cortex, hippocampus, hypothalamus, and striatum) at various ages were included.Results: Concentrations of taurine, total creatine (creatine + phosphocreatine), ascorbate, glucose and glutamate were consistently higher in male vs. female mice in most brain regions. Striatum was an exception with similar total creatine in male and female mice. The sex difference pattern in the hypothalamus was notably different from other regions. Interaction between sex and age was significant for total creatine and taurine in the cerebellum and hippocampus.Conclusions: Sex differences in regional neurochemical levels are small but significant and agedependent, with consistent male-female differences across most brain regions. The neuroendocrine region hypothalamus displays a different pattern of sex differences in neurochemical levels. Differences in energy metabolism and cellular density may underlie the differences, with higher metabolic rates in females and higher osmoregulatory and antioxidant capacity in males.